The responsive global organization : new insights from global strategy and international business - Andersen, Torben Juul (Emerald studies in global strategic responsiveness., 2017)
This book outlines the contours of the dynamic adaptive multinational corporation based on contemporary research insights from global strategy and international business. It considers the role of corporate leadership and frontline engagement to advance responsive innovation dealing with emergent risks and opportunities in turbulent global markets.